Thermal‐Disrupting Interface Mitigates Intercellular Cohesion Loss for Accurate Topical Antibacterial Therapy. Issue 12 (19th February 2020) - Hu, Benhui; Berkey, Christopher; Feliciano, Timothy; Chen, Xiaohong; Li, Zhuyun; Chen, Chao; Amini, Shahrouz; Nai, Mui Hoon; Lei, Qun‐Li; Ni, Ran; Wang, Juan; Leow, Wan Ru; et al.
Abstract: Bacterial infections remain a leading threat to global health because of the misuse of antibiotics and the rise in drug‐resistant pathogens. Although several strategies such as photothermal therapy and magneto‐thermal therapy can suppress bacterial infections, excessive heat often damages host cells and lengthens the healing time. Here, a localized thermal managing strategy, thermal‐disrupting interface induced mitigation (TRIM), is reported, to minimize intercellular cohesion loss for accurate antibacterial therapy. The TRIM dressing film is composed of alternative microscale arrangement of heat‐responsive hydrogel regions and mechanical support regions, which enables the surface microtopography to have a significant effect on disrupting bacterial colonization upon infrared irradiation. The regulation of the interfacial contact to the attached skin confines the produced heat and minimizes the risk of skin damage during thermoablation. Quantitative mechanobiology studies demonstrate the TRIM dressing film with a critical dimension for surface features plays a critical role in maintaining intercellular cohesion of the epidermis during photothermal therapy. Finally, endowing wound dressing with the TRIM effect via in vivo studies in S. aureus infected mice demonstrates a promising strategy for mitigating the side effects of photothermal therapy against a wide spectrum of bacterial infections, promoting future biointerface design for antibacterial therapy. Abstract : A localized thermal‐management strategy from thermal‐disrupting interface induced mitigation (TRIM) is developed to maintain intercellular cohesion and reduce function loss of epidermis tissue for topical antibacterial therapy. A dressing film with the TRIM effect inhibits aggregation of bacteria, promotes selective elimination of pathogens, and shortens the healing process.